2014
DOI: 10.1016/j.ophtha.2013.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Time to Clinically Significant Visual Acuity Gains after Ranibizumab Treatment for Retinal Vein Occlusion

Abstract: This retrospective analysis shows that more than 50% of patients treated with monthly ranibizumab achieved clinically significant vision gains during the initial 6 months of treatment, which largely were maintained using PRN treatment to 12 months. In comparison, less than 50% of patients initially randomized to sham (and later receiving ranibizumab 0.5 mg PRN treatment) ever achieved clinically significant vision gains. These results suggest that initiating treatment immediately after diagnosis may provide th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 23 publications
4
63
1
3
Order By: Relevance
“…There were 14 patients who received less than six total injections before the switch. Although the time for clinically significant VA gain in the CRUISE study was 5.2 months, 21 we decided to include patients in this study with a minimum of three prior injections of bevacizumab or ranibizumab based on the poor visual outcome of the early non-responders reported by Bhisitkul et al 8 The limitations of this study include the lack of standardized VA measurement, the lack of masking for the VA and OCT measurements, and the relatively small size of the study population. Its retrospective design naturally excludes a controlled environment for this cohort of patients as well as standardization of the treatment protocol.…”
Section: Discussionmentioning
confidence: 93%
“…There were 14 patients who received less than six total injections before the switch. Although the time for clinically significant VA gain in the CRUISE study was 5.2 months, 21 we decided to include patients in this study with a minimum of three prior injections of bevacizumab or ranibizumab based on the poor visual outcome of the early non-responders reported by Bhisitkul et al 8 The limitations of this study include the lack of standardized VA measurement, the lack of masking for the VA and OCT measurements, and the relatively small size of the study population. Its retrospective design naturally excludes a controlled environment for this cohort of patients as well as standardization of the treatment protocol.…”
Section: Discussionmentioning
confidence: 93%
“…For the treatment of cystoid macular oedema (CME) resulting from RVO, there are several options available like intravitreal injections of anti-vascular growth factor (anti-VEGF) substances such as ranibizumab, bevacizumab, and aflibercept in addition to retinal laser photocoagulation and intraocular corticosteroids [1, 2]. The BRAVO and CRUISE studies have shown a significant improvement of best corrected visual acuity (BCVA) after treatment with intravitreal ranibizumab [3-7]. In the RETAIN study, the visual acuity (VA) effect of ranibizumab was bigger in branch retinal vein occlusion (BRVO) than in central retinal vein occlusion (CRVO) after 4 years [8].…”
Section: Introductionmentioning
confidence: 99%
“…But data from the Standard Care vs Corticosteroid for Retinal Vein Occlusion (SCORE) trail also demonstrade limited benefit for laser therapy at 12 months with the median gain of six letters at 12 months. Furthermore, poor vision persists despite photocoagulation treatment in many patients, and its use is not recommended until 3 months after development of BRVO [18,19,31,32] .…”
Section: Macular (Grid) Laser Photocoagulationmentioning
confidence: 99%
“…Laser photocoagulation had been used for additional treatment in some studies such as in BRAVO study patients not achieving sufficient improvements at month 3 could receive laser therapy, even according to BVOS the benefits of laser therapy are minimal within the first year of treatment thus possibly confounding the results from month 3 onwards [30][31][32] .…”
Section: Macular (Grid) Laser Photocoagulationmentioning
confidence: 99%